The effect of psycho-education on resilience and anger control among pre-hospital emergency staff: A quasi-experimental study - Maryam Mohamadi Sadegh; Ali Navidian; Mahnaz Ghaljeh; Nasrin Rezaee (Tehran University of Medical Sciences, 2021)
Background & Aim: Pre-hospital emergencies are one of the most stressful medical professions. Stressful jobs affect employees' resilience and their ability to control anger. The aim of this study is to determine the effect of psycho-education on the level of anger and resilience among pre-hospital emergency staff. Methods & Materials: In this quasi-experimental study, 120 people employed in urban and road centers in Zahedan were included through the convenience sampling method. To determine the intervention and control group, out of 24 available centers, 12 centers were randomly assigned to the intervention group and 12 centers to the control group. First, a demographic information form and the self-reported anger and resilience questionnaires were completed by both groups. Then, the intervention group participated in five sessions of psycho-education in groups of 8-12 people. The questionnaires were completed again by both groups two months after the intervention. Data was analyzed by the SPSS software version 16 using descriptive (mean and standard deviation) and inferential statistics (Chi-square test, independent t-test and paired t-test). Results: The results of independent t-test showed no significant difference in the mean and standard deviation of resilience score among pre-hospital emergency staff between the intervention and control groups before the intervention (P=0.492), but after the intervention the difference was significant (P=0.009). Also, the results of independent t-test showed no significant difference in the mean and standard deviation of anger control score among pre-hospital emergency staff between the intervention and control groups before the intervention (P=0.672), but after the intervention, mean and standard deviation of anger control score in the intervention group were significantly higher than those of in the control group (P<0.001). Conclusion: The present study showed that psycho-education improved the resilience of emergency workers, and the employees were able to control their anger by enhancing resilience. It is suggested that in-service training programs for pre-hospital emergency staff include a psycho-education program to enhance resilience and control anger in those who face many stressful situations.